2021
DOI: 10.15835/nbha49112166
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation with Clariodeoglomus etunicatum improves leaf food quality of tea exposed to P stress

Abstract: The present study aimed to evaluate the effect of an arbuscular mycorrhizal fungus (AMF), Clariodeoglomus etunicatum, on leaf food quality and relevant gene expression levels of tea (Camellia sinensis cv. ‘Fuding Dabaicha’) seedlings exposed to 0.5 μM P (P0.5) and 50 μM P (P50) levels. Twenty-four weeks later, the seedlings recorded higher root mycorrhizal fungal colonization in P50 than in P0.5. AMF-inoculated tea plants represented significantly higher leaf fructose and glucose contents and lower sucrose con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
(38 reference statements)
2
9
0
Order By: Relevance
“…Low P levels favor root AM fungal colonization, but high P levels inhibit AM fungal colonization (Mora et al, 2008;Breuillin et al, 2010). The present study revealed that root mycorrhizal colonization rate was significantly lower at P 0 than at P 0.2 , which is consistent with the findings of Shao et al (2021), who reported that under P deficit conditions, P uptake by tea plants relied more on root hairs than on AM fungi, resulting in low AM fungal colonization under low P levels. Therefore, future work is needed to evaluate the response of root hairs and AM fungal colonization of P. cuspidatum to different P levels.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Low P levels favor root AM fungal colonization, but high P levels inhibit AM fungal colonization (Mora et al, 2008;Breuillin et al, 2010). The present study revealed that root mycorrhizal colonization rate was significantly lower at P 0 than at P 0.2 , which is consistent with the findings of Shao et al (2021), who reported that under P deficit conditions, P uptake by tea plants relied more on root hairs than on AM fungi, resulting in low AM fungal colonization under low P levels. Therefore, future work is needed to evaluate the response of root hairs and AM fungal colonization of P. cuspidatum to different P levels.…”
Section: Discussionsupporting
confidence: 93%
“…Inoculation with AM fungi also dramatically improved root average diameter, total length, and projected area independent of P levels, being superior at P 0.2 than at P 0 . Similar results were also observed in tea (Shao et al, 2021), walnut, and trifoliate orange exposed to P stress (Wu et al, 2015b;Huang et al, 2020). The improvement of root morphology triggered by AM fungi may be linked to the increase of root auxins and polyamine levels by AM fungi (Zhang et al, 2019;Zou et al, 2021).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Meanwhile, inoculation with C. etunicatum significantly improved the leaf water content and antioxidant enzyme activity of tea plants under drought stress ( Liu et al., 2020 ). In addition, AMF inoculation promoted the flavor and quality (e.g., catechins, amino acids, and tea polyphenols) of tea under phosphorus stress conditions ( Shao et al., 2018 ; Cao et al, 2021a ).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed that AMF had an important impact on nutrient uptake and physiological ecology in tea plants, manifested by increased chlorophyll content and leaf area, and reduced leaf water potential, thus enhancing plant water absorption capacity (Mathur et al, 2019). It can also significantly increase the mass fraction of proline, soluble protein, and glutathione glycopeptides, as well as the contents of various mineral nutrients required by tea plants, thereby improving the quality of tea (Cao et al, 2021). Based on these reports, it is of great importance to promote the positive effects of AMF on tea tree growth and to further research the effects of AMF on tea growth and quality under drought conditions, as well as the mechanisms of AMF on tea resilience.…”
Section: Introductionmentioning
confidence: 99%